Social preferences, accountability, and wage bargaining - Martin G. Kocher; Odile Poulsen; Daniel J. Zizzo (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
We assess the extent of preferences for employment in a collective wage bargaining situation with heterogeneous workers. We vary the size of the union and introduce a treatment mechanism transforming the voting game into an individual allocation task. Our results show that highly productive workers do not take employment of low productive workers into account when making wage proposals, regardless of whether insiders determine the wage or all workers. The level of pro-social preferences is small in the voting game, while it increases as the game is transformed into an individual allocation task. We interpret this as an accountability effect.
urn:nbn:de:bvb:19-epub-14039-5
Keywords: C91; C92; D71; J51; J52; 330; social preferences; wage bargaining; accountability; collective decision making; Soziale Wohlfahrtsfunktion; Verhandlungstheorie des Lohnes; Gewerkschaftspolitik; Arbeitsproduktivität; Neue politische Ökonomie; Theorie